Safety of paracetamol in osteoarthritis - Kaur, Jaspreet (2022)
Background Pain is one of the most troubling symptoms that warrant people with chronic conditions such as osteoarthritis (OA) to seek pharmacological treatment options. Paracetamol is currently the first-line drug recommended by most practice guidelines for managing pain in OA due to its perceived safety profile over other analgesics. Despite its modest effectiveness, the usage of paracetamol is widespread either as a prescription medication or over the counter drug for acute and chronic painful conditions. Nevertheless, the adverse effects have been overlooked in its long-term therapeutic usage. There is a growing controversy, highlighted in the National Institute for Health and Care Excellence OA (NICE) 2014 guidance on OA, that paracetamol is not as safe as thought previously, especially at the highest therapeutic dose of 4gm/day for the long term. Additionally, based on a limited number of studies, the association of gastrointestinal, cardiovascular, and renal events and all-cause mortality with the use of paracetamol is still unclear. Gaining knowledge of these adverse effects would help address this gap in the evidence and provide insights for clinical decision-making. Eventually, it might inform modification of the current recommendations and guidelines for chronic painful conditions such as OA and help clinicians discuss these side effects with patients when considering treatment with paracetamol.